Perforating Arteries of the Lemniscal Trigone: A Microsurgical Neuroanatomic Description - Tomasi, Santino Ottavio; Umana, Giuseppe Emmanuele; Scalia, Gianluca; Rubio-Rodriguez, Roberto Luis; Raudino, Giuseppe; Rechberger, Julian; Geiger, Philipp; Chaurasia, Bipin; Yaǧmurlu, Kaan; Lawton, Michael T.; Winkler, Peter A. (Frontiers in Neuroanatomy, 2021)
Background: The perforating arteries in the dorsolateral zone of the midbrain play a crucial role in the functions of the brain stem. Their damage due to herniation, pathological lesions, or surgery, favored by the narrow tentorial incisura, can lead to hemorrhages or ischemia, and subsequently to severe consequences for the patient. Objective: Not much attention has been directed to the perforating arteries in the lemniscus in the literature. The present study aims at a detailed analysis of the microanatomy and the clinical implica-tions of these vessels. We focused on the small vessels that penetrate the midbrain’s dorsolateral surface, known as lemniscal trigone, to understand better their microanatomy and their functional importance in the clinical practice during the microsurgical approach to this area. Methods: 44 alcohol-fixed postmortem human heads (87 hemispheres) without any pathological lesions provided the material for studying the perforating vessels and their origins around the dorsolateral midbrain using an operating microscope (OPMI 1 FC, Zeiss). Measurements of cali-bers and distances were taken using a digital caliper. Results: An origin from the SCA could be found as 70.11% (in 61 specimens) and from the PCA as 27,58% (in 24 specimens) of the hemispheres. The origin from the posterior choroidal artery was found in 4.54% (in 1 specimen). No perforating branches were discovered in 8.04% (in 7 specimens). Conclusions: Comprehensive understanding of the lemniscal trigone’s perforating arteries is vital to avoid the brainstem infarction during removal of the midbrain tumors and vascular malfor-mations.